A review of the porous transport layer in polymer electrolyte membrane water electrolysis. (17th April 2021) - Doan, Tuan Linh; Lee, Han Eol; Shah, Syed Shabbar Hassan; Kim, MinJoong; Kim, Chang‐Hee; Cho, Hyun‐Seok; Kim, Taekeun
Summary: Polymer electrolyte membrane water electrolysis (PEMWE) is the most promising and environmentally friendly method for highly pure hydrogen production when integrated into renewable energy sources. Presently, water electrolysis has merely 4% contribution to global hydrogen production owing to its economic challenges. To reduce the capital and operational cost of PEM water electrolysis, the porous transport layer (PTL) has been investigated intensively in the recent past. A PTL, sandwiched between a catalyst layer and a flow field, is responsible to transport water and oxygen on the anode side as well as hydrogen on the cathode side. In addition to the role of multiphase fluid transportation, PTL also acts as a current collector. A comprehensive insight into PTL materials, structural properties, and their function is strongly required for researchers to enhance performance and reduce the cost of PEMWE system. In this review, we widely discussed the findings on PTL's structural properties, surface modifications, and their impact on enhancing electrochemical performance and durability. In particular, the effect of pore size, porosity, pore gradient, thickness, and pretreatment on ohmic, mass transport, activation overpotential, and PTL modeling has been intensively analyzed. This review will unequivocally increase the previous understanding and open up an avenue for the development of state‐of‐the‐art PTL, thereafter advancing the commercialization of PEMWE. Abstract : Porous transport layer (PTL), where both the reactants/products of the electrochemical reaction and electrical transporting happens, plays an important function in a polymer electrolyte membrane water electrolysis (PEMWE) system. In this review, we widely discussed the findings on PTL's structural properties, surface modifications, and their impact on enhancing electrochemical performance and durability. This review will unequivocally increase the previous understanding and open up an avenue for the development of state‐of‐the‐art PTL, thereafter advancing the commercialization of PEMWE.